ADMINISTRATIVE JUSTICE: COMPARATIVE AND RUSSIAN CONTEXT - N. Bocharova (BRICS Law Journal)
International conference “Administrative Justice: Comparative and Russian Contexts” took place in Tyumen at the Tyumen State University on September 29–30, 2016 in the framework of the II Siberian Legal Forum devoted to the development of administrative legal proceedings in Russia.